On a regularization method for variational inequalities with P[0-indeks dolny] mappings - Konnov, Igor; Mazurkevič, Elena; Ali, Mohamed (Zielona Góra: Uniwersytet Zielonogórski)
We consider partial Browder-Tikhonov regularization techniques for variational inequality problems with P[0-indeks dolny] cost mappings and box-constrained feasible sets. We present classes of economic equilibrium problems which satisfy such assumptions and propose a regularization method for these problems.
Keywords: variational inequalities; partial regularization approach; P[0-indeks dolny] mappings